Healthy Living: Taking Care from Head to Toe - Linda B. Bobroff (EDIS)
If you have diabetes, pay special attention to your skin, eyes, teeth, gums, and feet. These areas are at high risk for complications. This 3-page fact sheet is a major revision that gives helpful information on ways to take care of these areas to reduce the risk of diabetes-related complications. Written by Linda B. Bobroff, and published by the UF Department of Family, Youth and Community Sciences, May 2016.